Immigration Enforcement and Domination: An Indirect Argument for Much More Open Borders. (March 2017) - Sager, Alex
Normative reflection on the ethics of migration has tended to remain at the level of abstract principle with limited attention to the practice of immigration administration and enforcement. This paper explores the implications of this practice for an ethics of immigration with particular attention to the problem of bureaucratic domination. I contend that migration administration and enforcement cannot overcome bureaucratic domination because of the inherent vulnerability of migrant populations and the transnational enforcement of border controls by multiple public and private actors. The implication is that even if restrictive immigration policies are permissible in principle, the attempt to enforce them leads to injustices that make them ethically unacceptable in practice.